CURVATURE DUCTILITYOF REINFORCED CONCRETE BEAM SECTIONS STIFFENED WITH STEEL PLATES (Journal of Engineering, 2024)
This paper presents theoretical parametric study of the curvature ductility capacity for reinforced concrete beam sections stiffened with steel plates. The study considers the behavior of concrete and reinforcing steel under different strain rates. A computer program has been written to compute the curvature ductility taking into account the spalling in concrete cover. Strain rate sensitive constitutive models of steel and concrete were used for predicting the moment-curvature relationship of reinforced concrete beams at different rate of straining. The study parameters are the yield strength of main reinforcement, yield strength of transverse reinforcement, compressive strength of concrete, spacing of stirrups and steel plate thickness. The results indicated that higher strain rates improve both the curvature ductility and the moment capacity of reinforced concrete beam sections. Moreover the section curvature ductility increases as the thickness of the stiffening plates decreases.